2018
DOI: 10.1007/s40430-018-1334-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of different aspect ratios for flow past three inline rectangular cylinders

Abstract: In this paper, numerical investigations are carried out to study the effect of aspect ratios (AR = length/height) for flow past three rectangular cylinders aligned inline at different gap spacings (g) using lattice Boltzmann method. The aspect ratio is varied between 0.25 and 3, gap spacing is taken in the range from 0.5 to 7 and the Reynolds number is fixed at 150. With the help of present numerical investigation, it is found that the variation of forces with different AR and g is governed by six distinct flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The flow around two tandem rectangular cylinders with distinct aspect ratios was simulated at Re = 100 by considering different values of G progressively varying from 0.25 to 20. From previous studies, we can conclude that the flow structure mechanism around multiple rectangular cylinders appears to be a complicated phenomenon that depends on several parameters, including Re, G, and AR (Islam et al, 2018;Rahman et al, 2021). In the current study, the resulting flow regimes are specified into different patterns in terms of the creation of different shape vortices, wake structure mechanism, and the behavior of shear layers detaching from cylinder corners and interacting with each other.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The flow around two tandem rectangular cylinders with distinct aspect ratios was simulated at Re = 100 by considering different values of G progressively varying from 0.25 to 20. From previous studies, we can conclude that the flow structure mechanism around multiple rectangular cylinders appears to be a complicated phenomenon that depends on several parameters, including Re, G, and AR (Islam et al, 2018;Rahman et al, 2021). In the current study, the resulting flow regimes are specified into different patterns in terms of the creation of different shape vortices, wake structure mechanism, and the behavior of shear layers detaching from cylinder corners and interacting with each other.…”
Section: Resultsmentioning
confidence: 68%
“…Therefore, we considered the 20-point grid for analysis for this study. This grid size follows recommendations based on lattice Boltzmann simulations for both single and multiple objects (Islam et al, 2018;Rahman et al, 2021). Note that the uniform meshing (Δx Δt 1) is selected in the whole computational domain because the standard LBM considers such meshing for simulations without any need to use external mesh generators (Perumal et al, 2012).…”
Section: Grid Independencementioning
confidence: 99%
See 1 more Smart Citation
“…The authors presented detailed wake patterns and force coefficient results for different geometrical configurations and Reynolds numbers. Islam, S. U., et al (Islam et al, 2018) presented a comprehensive numerical investigation into the aerodynamic behavior of three inline rectangular cylinders with varying AR = 0.25 to 3 and X G = 0.5 to 7 with Re = 150. They indicated that the AR significantly influences the flow behavior around the rectangular cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a smaller AR results in higher f D and lower vortex shedding frequencies, while a larger AR leads to the opposite trends. Islam et al [20] discussed the effect of AR ranging from 0.25 to 3 and G ranging from 0.5 to 7 on the flow characteristics of three inline rectangular cylinders with fixed Re = 150. The results showed that the AR strongly affected the force coefficients ( C f ) of the cylinders.…”
Section: Introductionmentioning
confidence: 99%